Facial Morphology and Occlusion at the Stage of Early Mixed Dentition in Cleft Palate Patients Treated with Furlow Palatoplasty - HAYATSU, Makoto; HANADA, Kooji; ISHII, Kazuhiro; ASAHITO, Toshikazu; TAKAGI, Ritsuo; IIDA, Akihiko; MORITA, Shuichi; IMAI, Nobuyuki; ONO, Kazuhiro (Journal of Japanese Cleft Palate Association, 2001)
Facial morphology and occlusion at the stage of early mixed dentition in cleft palate patients treated with Furlow palatoplasty were examined and compared with patients treated with the pushback procedure. The subjects selected for this study were 15 patients with a cleft of the soft palate, who were divided into two different groups: The Furlow group consisted of 3 male and 5 female patients, whose cleft palates were repaired with Furlow double-opposing Z-plasty, at an average age of 1 year and 8 months, and the pushback group consisted of 2 male and 5 female patients, whose cleft palates were closed with the pushback procedure, at an average age of 1 year and 7 months. Cephalometric radiographs (mean age,8 years for the Furlow group, and 7 years and 11 months for the pushback group) and dental study casts (mean age,7 years and 10 months for the Furlow group, and 8 years for the pushback group) were analyzed. Six angles and 4 distances were measured in the cephalograms, and 9 measurements of dental arch width and 2 measurements of dental arch length, were obtained. The results indicated that midfacial growth was significantly better (angle ANB, angle NAPog, distance A' -Ptm' ) and upper dental arches were significantly larger (inter deciduous canine distance, inter first and second deciduous molar distances, dental arch length) in the Furlow group, compared with the pushback group. No subject in the Furlow group had crossbite, while in the pushback group,6 of 7 subjects had anterior and/or posterior crossbite. As Furlow palatoplasty avoids the need for a lengthening procedure that uses mucoperiosteal flaps from the hard palate, it could allow adequate maxillary growth.